Quality improvement project to improve inhaler delivery in the intensive care unit - QinHao Jonathan Ye; Ganesh Kalyanasundaram; Hsiao Peng Toh; Qian Wen Leo; Linda Marie Nathan; Aubrey Cunanan; Han Ying Jessica Tan; Kiran Sharma (Proceedings of Singapore Healthcare, 2024)
Background Late 2022, an ICU nurse discovered that Seretide™ (salmeterol/Fluticasone) Evohaler, a commonly used inhaler, did not change its dose counter when used with the inhaler connector 22M-22F. This was identified as a medication safety issue. Knowledge gaps of inhaler use in mechanically ventilated patients were identified as well. Aims To effectively administer metered dose inhalers to ventilated patients and increase its accuracy and safety. Methods We instituted education programs for healthcare professional in the ICU and introduced a new inhaler connector RTC 24-V. This was compared with the existing 22M-22F connector in a comparative study. Results The dose counter of Seretide™ recorded prior to initiation and extubation showed an obvious drop in doses ranging from 15 to 63 in patients randomized to use RTC 24-V, compared to 0 to 2 drop in doses for patients using 22M-22F. A total of 51 pre study and 33 post study questionnaires were completed. Confidence that the accurate dose of medications was administered rose from 58.8% to 84.8% after using the RTC 24-V. Responses that there was no issue compromising patient safety rose from 0% to 51.5% and fewer staff expressed concern about disconnections causing infections, dropping from 51% to 9.1%. 93.9% of respondents chose the new RTC 24-V as the preferred inhaler connector. Conclusion The new inhaler connector RTC 24-V was assessed to have less medication errors. ICU healthcare professionals expressed greater confidence in its safety and accuracy. We will implement the use of this connector with continued medical education.